Increasing Interpersonal Interactions in an Online Course: Does Increased Instructor E-mail Activity and a Voluntary In-Person Meeting Time Facilitate Student Learning? - Cung, Bianca; Xu, Di; Eichhorn, Sarah (Online Learning, 2018)
Distance learning is expanding rapidly in universities. While theoretical and qualitative literature stress the critical role of effective interpersonal interactions in motivating students and facilitating learning in online environments, quantitative evidence on the benefits of increased interpersonal interactions on student learning outcomes is limited. This study examines the effect of providing a voluntary meeting time and increasing instructor e-mail activity on student grades in a fully online Pre-Calculus course at a public university. Student selection into courses was minimal since students only had access to one condition at a time. We further use a propensity score matching strategy to address demographic variations in student characteristics across cohorts. Our results indicate that the increased interpersonal interaction opportunities increased final exam scores by 0.22 standard deviations and improved passing rates by 19 percentage points. The Rosenbaum’s sensitivity analysis indicates that it is unlikely that these results are due to omitted variable bias.